Empowering Gili Ketapang Island: Dissemination of Environmentally Friendly Photovoltaic Technology to the Young Generation - Yoyok Cahyono; Yanurita Dwihapsari; Malik Anjelh Baqiya; Heru Sukamto; Zainal Arifin; mochamad zainul Asrori; Sri Yani Purwaningsih; Bintoro Anang Subagyo; Mochamad Zainuri; Agus Purwanto; Suminar Pratapa; Heny Faisal; Suasmoro Suasmoro; Darminto Darminto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Solar Cell Research Group, which is under Advanced Materials Research Group, Department of Physics, Faculty of Science and Data Analytics, ITS Surabaya, with its competency and research, tries to be actively involved in contributing and providing alternative solutions to problems in society, especially regarding the problem of global warming and energy crisis. One of the concrete actions is through community education activities to increase understanding and awareness of the use of environmentally friendly photovoltaic technology on Gili Ketapang Island, Probolinggo. This island is one of the most populous small islands in Indonesia with the problem of ‘high-cost electricity from the state electricity company. The training materials provided for this activity include the Qur’an and Science, global warming, energy crisis, and renewable energy, and the use of photovoltaic energy technology. Thus, the understanding, awareness, and independence of the community of Gili Ketapang Island in the electricity sector can be improved by utilizing renewable energy sources, especially photovoltaic technology. In the long term, the role of various renewable energies in the future is expected to be more significant on this island by utilizing this abundant solar energy